Analisis Kompetensi Mahasiswa Menjadi Amil Zakat Profesional (Studi Pada Mahasiswa Prodi Manajemen Zakat dan Wakaf IAIN Bengkulu) - Yenti Sumarni; Endang Mustika (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The purpose of this study was to determine the competencies possessed by students of the Zakat and Waqf Management Study Program to become candidates for professional zakat amil, while the types of data used were secondary data and primary data, using a qualitative approach. Based on the results of research and discussion, it can be concluded that the competencies that must be possessed by zakat and waqf management students are mastering the science of zakat fiqh, mastering managerial knowledge about zakat management, namely collection, distribution and utilization and reporting of zakat, amil must also have skills in the IT field and accountability in calculating zakat funds. on the reality in the field that students of zakat and waqf management study programs are already competent in the field of zakat fiqh science but are not yet competent in the field of fundrising practice and zakat information system technology.┬á